Enantioselective one-pot rhodium-catalyzed cycloisomerization-Wittig sequence to chiral functionalized 4-alkyl 3-alkylidene tetrahydrofuran(on)es - Körber, Nadine; Rominger, Frank; Müller, Thomas J. J. (Synlett, 2010)
Alkyl and (hetero)aryl alkyne allyl alcohols can readily be transformed into chiral 4-alkyl 3-alkylidene tetrahydrofurans and tetrahydrofuranones bearing α,β-unsaturated carbonyl side chains in a one-pot fashion via an enantioselective rhodium-catalyzed cycloisomerization-Wittig olefination sequence in good yields (54-86%).